Clinical application of calculated split renal volume using computed tomography‐based renal volumetry after partial nephrectomy: Correlation with technetium‐99m dimercaptosuccinic acid renal scan data. (22nd March 2017) - Lee, Chan Ho; Park, Young Joo; Ku, Ja Yoon; Ha, Hong Koo
Abstract : Objective: To evaluate the clinical application of computed tomography‐based measurement of renal cortical volume and split renal volume as a single tool to assess the anatomy and renal function in patients with renal tumors before and after partial nephrectomy, and to compare the findings with technetium‐99m dimercaptosuccinic acid renal scan. Methods: The data of 51 patients with a unilateral renal tumor managed by partial nephrectomy were retrospectively analyzed. The renal cortical volume of tumor‐bearing and contralateral kidneys was measured using ImageJ software. Split estimated glomerular filtration rate and split renal volume calculated using this renal cortical volume were compared with the split renal function measured with technetium‐99m dimercaptosuccinic acid renal scan. Results: A strong correlation between split renal function and split renal volume of the tumor‐bearing kidney was observed before and after surgery ( r = 0.89, P < 0.001 and r = 0.94, P < 0.001). The preoperative and postoperative split estimated glomerular filtration rate of the operated kidney showed a moderate correlation with split renal function ( r = 0.39, P = 0.004 and r = 0.49, P < 0.001). The correlation between reductions in split renal function and split renal volume of the operated kidney ( r = 0.87, P < 0.001) was stronger than that between split renal function and percent reduction in split estimated glomerular filtration rate ( r = 0.64, P < 0.001). Conclusions: The split renal volume calculated using computed tomography‐based renal volumetry had a strong correlation with the split renal function measured using technetium‐99m dimercaptosuccinic acid renal scan. Computed tomography‐based split renal volume measurement before and after partial nephrectomy can be used as a single modality for anatomical and functional assessment of the tumor‐bearing kidney.